A bibliometric analysis and review of recent researches on TRPM7. Issue 1 (1st January 2020) - Zhang, Shiqi; Zhao, Dongyi; Jia, Wanying; Wang, Yuting; Liang, Hongyue; Liu, Lei; Wang, Wuyang; Yu, Zhiyi; Guo, Feng
ABSTRACT: The transient receptor potential melastatin-subfamily member 7 (TRPM7) is a ubiquitously expressed protein that contains both an ion channel and an active kinase. TRPM7 has involved in a variety of cellular functions and critically participates in various diseases mainly including cancer and neurodegenerative disorders. However, the theme trends and knowledge structures for TRPM7 have not yet been studied bibliometrically. The main purposes of this research are to compare the scientific production in the research field of TRPM7 among countries and to evaluate the publication trend between 2004 and 2019. All publications were extracted from the Web of Science Core Collection (WoSCC) database from 2004 to 2019. Microsoft Excel 2018, Prism 6, and CiteSpace V were applied to analyze the scientific research outputs including journals, countries, territories, institutions, authors, and research hotspots. In this report, a total of 860 publications related to TRPM7 were analyzed. Biophysical Journal ranked top for publishing 31 papers. The United States of America had the largest number of publications (320) with a high citation frequency (11, 298) and H-index (58). Chubanov V (38 publications) and Gudermann T (38 citations), who from Ludwig Maximilian University of Munich, were the most productive authors and had the greatest co-citation counts. Our study also combined the bibliometric study with a systematic review on TRPM7, highlighting the four research frontiers of TRPM7. This is the first study that demonstrated the trends and future development in TRPM7 publications, providing a clear and intuitive profile for the contributions in this field.